(3GdJShjb GdRQGYj (B/s - (3YHjOGJ, eMeOs ((3YeGf(B: s (3OGQ hGFd ddfTQ(B, s, 2005)
(3ebOeI aj GdJShjb GdRQGYj,CSGdjH OQGSI GdCShGb GdRQGYjI,JShjb GdEfJGL GdRQGYj,JShjb hGSJgdGc GdSdY GdZPGFjI,eYGdLI hJUfjY GdCZPjI,JLGQI GdLedI hGdJLRFI aj eLGd GdUfGYI GdZPGFjI,JOQjL hJUfja GdefJLGJ GdRQGYjI,JNRjf GdefJLGJ GdRQGYjI hGdZPGFjI,GdJShjb GdOhdj hGdefGaSI aj eLGd GdEfJGL GdRQGYj hGdZPGFjs
(3HHdjhZQGajG(B:(3U U(B.247-250s
Keywords: (3GdGfJGL GdRQGYj(B-(3JShjbs